Integrating Eco-Theological Values into Islamic Religious Education in Adiwiyata Schools - ainul muttaqin, muhammad; Sulaeman (TA`DIBUNA, 2026)
The global environmental crisis demands educational interventions capable of fostering ecological awareness and sustainable behavior. This study aims to analyze the integration of eco-theological values into Islamic Religious Education at SMPN 11 Makassar, an Adiwiyata (eco-friendly) school. A qualitative case study approach was employed, involving interviews, classroom observations, and document analysis with teachers, students, and school administrators. The findings show that Islamic Education teachers integrate eco-theological values by linking Qur’anic verses with environmental issues, applying project-based learning, and modeling environmentally responsible behavior. These values are also embedded in key subjects such as aqidah, fiqh, and akhlak, and are reinforced by school policies and multi-stakeholder collaboration. The main challenges, students’ inconsistent behavior outside school and limited facilities, are addressed through partnerships and participatory programs. In conclusion, the eco-theological approach in Islamic Religious Education offers a contextual, values-based model for sustainability education that can be replicated in other school settings.